Evaluasi dampak pencemaran mikroplastik pada sistem budidaya perikanan: Strategi pengelolaan berkelanjutan - Yusuf, Muh. Amri; Effendi, Irzal (Universitas Sam Ratulangi, 2024)
Microplastic (MP) pollution presents a significant challenge to the sustainability of aquaculture. MPs, originating from various sources such as domestic plastic waste and the degradation of aquaculture equipment, have been detected in aquaculture media, including water and sediment. Cultured organisms like fish, shrimp, and seaweed exhibit MP accumulation, impacting their health and posing risks to human consumers. This study reviews the distribution, ecological impacts, and potential mitigation strategies for MPs in aquaculture environments. Findings reveal that MPs cause bioaccumulation and trophic transfer, leading to physiological disturbances in organisms. Moreover, MPs act as carriers for other harmful pollutants. Mitigation technologies, such as water filtration systems and biodegradable materials, are under development but require further evaluation. Biological approaches utilizing microorganisms for MP degradation offer sustainable solutions. This study recommends integrated management through technological innovation, policy development, and community-based approaches to mitigate MP impacts in aquaculture. These measures are crucial to ensuring food safety and environmental sustainability. Keywords: microplastics, aquaculture, mitigation, environment, sustainability